Synthesis, characterization and photocatalytic activity of 1D TiO2 nanostructures - Cabrera, J (2014)
Nanowire/nanorod TiO2 structures of approximately 8 nm in diameter and around 1,000 nm long were synthesized by alkaline hydrothermal treatment of two different TiO2 nanopowders.